PREVENTION, PROXIES, AND THE LIMITS OF SELF-DEFENCE: INTERNATIONAL LAW AND THE SECURITY DILEMMA IN THE ISRAEL–IRAN RIVALRY - Đekić, Aleksandar (The Review of International Affairs, 2026)
This article examines how power, discourse, and law interact to drive escalation in the Israel–Iran rivalry. It asks under what conditions a claim of self-defence crosses into unlawful prevention. The framework combines structural realism, offensive realism, and securitization theory with doctrinal analysis of Article 51 of the United Nations Charter and key International Court of Justice rulings. The June 2025 strikes sequence serves as case study, drawing on UN debates, public statements, and open-source intelligence. Findings indicate three overlapping dynamics. First, structural insecurity incentivises anticipatory action: Israel institutionalised preventive logic as strategic culture. Second, securitizing speech acts, such as Iran’s existential rhetoric, transform threats into justification for extraordinary measures. Third, legal criteria of imminence, necessity, and proportionality are repeatedly stretched, especially when nuclear infrastructure and proxy networks are involved. International humanitarian law further limits proportionality, yet its application proved fragile in practice. The study proposes stricter evidentiary burdens for imminence, a “proportionality-plus” test for nuclear sites, and inclusion of proxies in necessity assessments. Together, these adjustments would narrow misuse of self-defence and strengthen legal restraint in high-risk rivalries.